Verbal Representation Analysis in Jasaraharja and Prudential Insurance TV Commercials - Nada Veronita; Hamzah Hamzah (Universitas Negeri Padang, 2022)
Multimodality is a study that studies how a meaning is formed from different modes simultaneously both verbally and visually. In this study, we analyze the differences in meaning in verbal analysis on insurance advertisements for Jasaraharja and Prudential insurance advertisements. This study aims to find differences in the verbal meaning of the two insurance advertisements using the Systemic Functional Linguistics theory of Halliday and Manthiessen (2004). The method used in this study is a qualitative descriptive method. The results showed that in Jasaraharaja advertisements, verbal use, both oral and written, was higher than in Prudential advertisements. The results showed that there were some differences in the two advertisements in using Systemic Functional Linguistics, namely the analysis of mental affective process, mental perceptive process, existential processes, exclamative, affect happiness, affect security, affect satisfaction, judgment social esteem negative, appreciation positive, negative appreciation, low probability, low high usuality high inclination, high obligation, conjunctive theme and wh-question theme. The differences are dominated by Jasaraharja insurance advertisements.